Diet and Abundance of Bobcat (Lynx rufus) in the Potosino-Zacatecano Plateau, Mexico - Sánchez-González, Raúl; Hernández-Saint Martin, Anuar David; Rosas Rosas, Octavio César; García-Chávez, Juan (THERYA, 2018)
The Potosino-Zacatecano Plateau (PZP) is characterized by a system of hills surrounded by ridges where the bobcat is the only wild felid; however, there is no information on the basic ecology of this species in this region. The objective of this work was to determine the diet and abundance of the bobcat in Cerro del Peñón Blanco, San Luis Potosí. The diet was inferred from the analysis of prey remains in feces; in addition, the minimum number of bobcats in the study area was estimated by camera traps placed in Cerro del Peñón Blanco, San Luis Potosí. Diet composition was expressed as percentage of occurrence. Individual bobcats were identified by the distinctive morphological characteristics of each. Seventy five scat samples were collected and analyzed. The diet included 14 taxa, with the rabbit Sylvilagus audubonii as the species most frequently consumed. The mouse Peromyscus spp. was the rodent species with the highest frequency of occurrence; however, no single species was dominant. We identified seven bobcat individuals: three males, three females and one of unknown sex. The bobcat diet allows inferring how this feline uses landscape in the study area, feeding on its main prey in foothills fragmented patches and complementing its diet with prey present in Peñón Blanco. The study area still provides sufficient prey base for the bobcat.